Dynamics and heat diffusion of Abrikosov's vortex-antivortex pairs during an annihilation process - Duarte, E. C.S. [UNESP]; Sardella, E. [UNESP]; Ortiz, W. A.; Zadorosny, R. [UNESP] (IOP Publishing, 2017)
The manipulation and control of vortex states in superconducting systems are of great interest in view of possible applications, for which mesoscopic materials are good candidates. In this work, we studied the annihilation dynamics and the dissipative aspects of an Abrikosov's vortex-antivortex pair in a mesoscopic superconducting system with a concentric hole. The generalized time-dependent Ginzburg-Landau equations were numerically solved. The main result is the appearance of a phase slip-like line due to the elongation of the vortex and antivortex cores. Under specific circumstances, thermal dissipation might be associated with a sizeable relaxation of the order parameter, so that the energy released in the annihilation of a vortex-antivortex pair might become detectable in measurements of the magnetization as a function of time.
Keywords: annihilation; energy dissipation; heat diffusion; TDGL; vortex dynamics